A new approach in the treatment of pediatric hypertrophic burn scars: Tixel‐associated topical triamcinolone acetonide and 5‐fluorouracil delivery. (19th October 2019) - Artzi, Ofir; Koren, Amir; Niv, Roni; Mehrabi, Joseph N.; Mashiah, Jacob; Friedman, Or
Abstract: Background: Pediatric hypertrophic burn scars are challenging to treat due to their widespread nature and pain associated with the treatment. Intralesional triamcinolone acetonide (TAC) injection with or without 5‐fluorouracil (5FU) is considered first‐line treatment for severe hypertrophic scars. The pain associated with the procedure, the uneven topography, and epidermal atrophy, all limit the application of this treatment modality. Aims: We sought to evaluate the clinical effectiveness and safety profile of a novel thermomechanical system (Tixel, Novoxel) for transdermal delivery of a topical solution containing TAC and 5‐FU in the treatment of hypertrophic scars. Patients/Methods: A retrospective study of pediatric hypertrophic burn scars treated between 2015 and 2017 was performed. Epidemiologic, treatment data, effectiveness score, and safety were reviewed. Results: Four children (one male and three females, ages 3‐10 years old) with hypertrophic burn scars treated with the Tixel device were evaluated. Mean scar VSS was reduced from 8.4 ± 0.8‐5.2 ± 0.5 ( P ‐value – .001) after eight treatments. The mean improvement of toughness, thickness, color, and general aesthetic impression was 3.1 ± 0.43 → 2.2 ± 0.31, 3.4 ± 0.5 → 1.9 ± 0.63, 2.7 ± 0.21 → 2.4 ± 0.25, and 3.23 ± 0.44 → 1.6 ± 0.64, respectively. Mean treatment pain VAS score was 1.74 ± 0.9. Patient's parents rated their satisfaction level as "moderate‐high." No topical or systemic complications were observed. Conclusion: Thermomechanical decomposition of the stratum corneum, in combination with topical application of TAC and 5‐FU, is a safe, relatively painless, and efficient modality for the treatment of pediatric hypertrophic burn scars.